A Comparison of Performance among Exotic Meat Strains and Local Chicken Ecotypes under Sudan Conditions - Binda, B.D.; Yousif , I.A.; Elamin, K.M.; Eltayeb, H.E. (International Journal of Poultry Science, 2012)
The present study was conducted to compare the performance of exotic meat strains (Hybro and Hubbard) and native chicken ecotypes (Bare- neck, Large Beladi and Betwil) under hot climate of the Sudan. A total of 505 one day old chicks were reared together using a Completely Randomized Design with 9 replicates for each genotype. Traits studied up to 8 weeks of age were body weight, feed intake, live weight gain, feed conversion ratio and mortality. Results revealed that there were significant differences (p<0.01) for body weight at various ages among the different genotypes. Body weights for the exotic strains at hatch, 4 and 8 weeks were in the range of 37.85±2.23 - 39.76±3.77, 497.37±101.50 - 516.25±107.95 g and 1230.46±258.06 - 1269.63±242.16 g respectively, whereas the corresponding results for the local ecotypes were 24.68±2.60 - 27.83±4.24, 109.28±25.77 - 141.53±33.75 g and 271.90±25.18 - 341.73±63.77 g. Average live weight gain during the first 4 weeks of age (starter stage) was significantly lower than that during the second 4 weeks (finisher stage) for both exotic strains and native ecotypes. Hybro strain exhibited the highest total live weight gain (1231.78 g.) whereas Large Baladi ecotype was the lowest (247.22). Feed intake and feed conversion ratio showed significant differences (p<0.01) between the exotic strains and the local ecotypes with the former consumed amount of feed three times that consumed by the latter and had better feed efficiency. Although the overall mortality and mortality during the first 4 weeks of age were higher among the local ecotypes than those of the exotics, the reverse was true during the second 4 weeks of age. It can be concluded that the performance of the exotic strains was substantially higher than that of the local chicken ecotypes. This can be attributed to the unimproved genetic potentials of the local chicken ecotypes. On the other hand, the performance of the exotic strains was also lower than that which can be expected under optimum environmental conditions. This may be due to the effect of high ambient temperature.